Schwann Cell‐Specific Ablation of Beclin 1 Impairs Myelination and Leads to Motor and Sensory Neuropathy in Mice - Lisa Gambarotto; Loris Russo; Silvia Bresolin; Luca Persano; Rachele D'Amore; Giulia Ronchi; Federica Zen; Luisa Muratori; Alice Cani; Samuele Negro; Aram Megighian; Sonia Calabrò; et al. (Advanced Science)
Abstract The core component of the class III phosphatidylinositol 3‐kinase complex, Beclin 1, takes part in different protein networks, thus switching its role from inducing autophagy to regulating autophagosomal maturation and endosomal trafficking. While assessed in neurons, astrocytes, and microglia, its role is far less investigated in myelinating glia, including Schwann cells (SCs), responsible for peripheral nerve myelination. Remarkably, the dysregulation in endosomal trafficking is emerging as a pathophysiological mechanism underlying peripheral neuropathies, such as demyelinating Charcot‐Marie‐Tooth (CMT) diseases. By knocking out Beclin 1 in SCs here a novel mouse model (Becn1 cKO) is generated, developing a severe and progressive neuropathy, accompanied by involuntary tremors, body weight loss, and premature death. Ultrastructural analysis revealed abated myelination and SCs displaying enlarged cytoplasm with progressive accumulation of intracellular vesicles. Transcriptomic and histological analysis from sciatic nerves of 10‐day and 2‐month‐old mice revealed pro‐mitotic gene deregulation and increased SCs proliferation at both stages with axonal loss and increased immune infiltration in adults, well reflecting the progressive motor and sensory functional impairment that characterizes Becn1 cKO mice, compared to controls. The study establishes a further step in understanding key mechanisms in SC development and points to Beclin 1 and its regulated pathways as targets for demyelinating CMT forms.